Complications and pregnancy outcome following uterine compression suture for postpartum haemorrhage: A single centre experience. (July 2014) - Liu, S.; Mathur, M.; Tagore, S.
Abstract In the treatment of postpartum haemorrhage from uterine atony, uterine compression sutures, such as the B-Lynch suture and its modifications have a role with the advantage of preservation of the uterus for fertility. There is however, a risk that apposition of the anterior and posterior walls of the uterus will impede drainage of lochia, resulting in undesirable complications. We undertook a five-year retrospective study of all women who underwent uterine compression sutures at the KK Women's and Children's Hospital, between 2008 and 2012. In total, 23 women had uterine compression sutures during the study period, of which, nineteen women managed to conserve their uterus. Our complication rate was 25%, which included persistent vaginal discharge, pyometra and endometritis. There were three conceptions, with two successful pregnancies. Our study shows uterine compression suture to be a safe and effective alternative to avoid hysterectomy with preservation of fertility at the time of major postpartum haemorrhage. The outcome of subsequent pregnancies is reassuring.